Prediksi Return Emerging Market di Indonesia Dan Malaysia - Ossi Ferli (FEB Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this research is to models daily returns with conditional heterocedasticity to investigate the volatility of returns by using mean process model of AR(1) and comparing two conditional variance model EGARCH and GARCH (1,1) of Indonesia and Malaysia stock index market. The result of the research are EGARCH are a better predictor for return volatility of Indonesia and Malaysia.